Clinicoradiopathologic Analysis of Odontomas: A Retrospective Study of 242 Cases - Katherine A. DeColibus; D. Shane Rasner; Osariemen Okhuaihesuyi; Adepitan A. Owosho (MDPI AG, 2023)
Odontomas are considered hamartomatous lesions and are one of the two most common odontogenic tumors of the jaw. Odontomas are classified as compound or complex. Recently, ameloblastic fibro-odontoma (AFO) and ameloblastic fibro-dentinoma were reclassified as developing odontomas. Though clinically odontomas are usually asymptomatic, they have adverse effects on adjacent teeth such as tooth impaction, delayed eruption, displacement of teeth, over-retention of teeth, and can give rise to odontogenic cysts within the jaw. We sought to evaluate the clinicoradiopathologic presentations of odontomas by collecting and analyzing the clinical, radiographic, and pathologic data of odontomas diagnosed in our institution from 2013 to 2022. Over this 10-year period, there were 242 patients with a histopathological and/or radiographic diagnosis of odontoma. There was no gender predilection and ages ranged from 3 to 101 years (median, 14 years). The second decade of life was the most prevalent (57.4%). There was no jaw predilection; however, the anterior jaw was the most common location. Ninety-four (38.8%) cases presented with clinical findings. The most common finding was tooth impaction (n = 83). Nine (3.7%) cases were histopathologically confirmed to be associated with other lesions such as dentigerous cysts (n = 8) and nasopalatine duct cyst (n = 1). The median age (25 years) of patients diagnosed with odontomas associated with cysts was older than patients with odontomas (14 years) without associated cysts. Compound odontomas were the most common type of odontoma compared to complex and AFOs with 71.4%, 26.6%, and 2%, respectively. The majority of compound odontomas involved the anterior jaw (69.3%) and mandible (54.9%) while the majority of complex odontomas involved the posterior jaw (59.6%) and maxilla (54.7%). The four AFOs were in the posterior jaw and 75% involved the maxilla. The median age (12 years) of patients diagnosed with AFO was the youngest compared to patients diagnosed with compound (13 years) and complex (16 years). In conclusion, we analyzed the clinical, radiographic, and pathologic features of 242 new cases of odontomas. Our study reaffirms that odontomas frequently affect the pediatric population and can disrupt their dentition. Based on the result of this study, our clinical recommendation to prevent problems to adjacent teeth from odontomas is for dentists to be apt in the diagnose of odontomas to ensure that they are surgically removed in a timely manner.